KEPATUHAN MINUM OBAT PASIEN HIPERTENSI PESERTA JKN DI INSTALASI RAWAT JALAN RUMAH SAKIT SITI KHODIJAH KOTA PEKALONGAN - Aqilatul Maziah; Fef Rukminingsih; Paulina Maya Octasari (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2024)
Hypertension is the highest case of non-communicable diseases (NCDs) in Pekalongan City. Uncontrolled hypertension can increase the risk of morbidity and mortality. Taking antihypertensive medication regularly can control the blood pressure of hypertensive patients so compliance with taking medication is the main factor that influences the success of therapy. This study aims to determine the medication compliance of hypertensive patients who are national health insurance participants at the Outpatient Installation of Siti Khodijah Hospital, Pekalongan City. This research is a descriptive observational study with a cross-sectional design. The sampling technique used is accidental sampling. Compliance was measured using the MMAS-8 (Morisky Medication Adherence Scale) questionnaire. Respondents were hypertensive patients in the outpatient installation of Siti Khodijah Hospital, Pekalongan City, aged ≥26 years, who were National Health Insurance participants and underwent examinations in March-April 2023. The data was analyzed qualitatively and quantitatively. The results revealed that of the 260 respondents consisting of 150 female patients and 110 male patients, most of the patients were ≥46 years old (91.92%), had an educational background of elementary school graduates (32.7%), high school (32.3%) and higher education (35%). A total of 67 respondents were housewives (25.77%) and 47 respondents did not work (18.07%). Meanwhile, others work in various professions such as teachers/lecturers, state civil servants, private employees and entrepreneurs. The adherence to taking medication for hypertensive patients at the Outpatient Installation of Siti Khodijah Hospital, Pekalongan City, was 82.31% compliant and 17.69% non-compliant. Patients aged ≥46 years were more compliant. Adherence to taking medication decreases as the duration of taking medication increases and the number of medications taken increases.